2018
DOI: 10.1016/j.dib.2018.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Data supporting Ni-NTA magnetic bead-based fluorescent protease assay using recombinant fusion protein substrates

Abstract: Data provided here are related to the research article entitled as ‘A recombinant fusion protein-based, fluorescent protease assay for high throughput-compatible substrate screening’. Here we describe data related to the investigation of the properties of the His6-MBP-VSQNY↓PIVQ-mApple recombinant protein substrate and its interactions with Ni-NTA magnetic beads, including the dependence of substrate attachment on incubation time and concentration. Data on the folding efficiency and conformational stability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 4 publications
2
22
0
Order By: Relevance
“…The individual optimization of the assay may be limited only by the compatibility of the affinity beads with the applied conditions, reagents, and additives. In agreement with the manufacturer's protocol, we also found that the affinity binding of substrates to the Ni-NTA bead surfaces substantially weakens at pH ≤ 6.5 15 . Therefore, it is recommended to apply substrate blank samples parallel to the reaction samples, and the rate of spontaneous substrate dissociation needs to be considered during the evaluation of results.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The individual optimization of the assay may be limited only by the compatibility of the affinity beads with the applied conditions, reagents, and additives. In agreement with the manufacturer's protocol, we also found that the affinity binding of substrates to the Ni-NTA bead surfaces substantially weakens at pH ≤ 6.5 15 . Therefore, it is recommended to apply substrate blank samples parallel to the reaction samples, and the rate of spontaneous substrate dissociation needs to be considered during the evaluation of results.…”
Section: Discussionsupporting
confidence: 86%
“…ii) Termination of reaction samples. Another advantage of the method is that the enzymatic reaction can be terminated without the use of heat denaturation treatment or any potentially interfering chemical agents 15 . The termination can be carried out simply by separating the magnetic beads from the reaction mixture, using a conventional magnetic particle concentrator.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the synthetic oligonucleotides widely used in protease assays, fluorescent proteincontaining substrates were also used in activity measurements. The applied fluorimetric protease assay has been designed and tested previously on HIV-1 and TEV PRs [31][32][33], and we successfully adapted it for the investigation of Ty1 PR. The previously designed pDest-His 6 -MBP-mTurquoise2 expression vector [31][32][33] has been modified to contain the coding sequence of a (GGGGS) 4 linker.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant fluorescent substrates were expressed in E. coli BL21(DE3) cells as previously reported [31][32][33]. The His 6 -tagged fluorescent recombinant protein substrates were purified from the supernatant of the lysed cells by the addition of Ni-NTA magnetic agarose beads (Qiagen) and were incubated for 30 min while continuously shaking.…”
Section: Expression and Purification Of Fluorescent Substratesmentioning
confidence: 99%
See 1 more Smart Citation